Family history of cancer and head and neck cancer survival. (7th March 2017) - Getz, Kayla R.; Rozek, Laura S.; Peterson, Lisa A.; Bellile, Emily L.; Taylor, Jeremy M. G.; Wolf, Gregory T.; Mondul, Alison M.
Abstract : Objective: Patients with a family history of cancer may be genetically predisposed to carcinogenesis. This could affect risk of recurrence, second primary tumors, and overall outcomes after treatment of a primary cancer. We evaluated the association between family history of cancer and disease‐specific survival in a cohort of patients with primary head and neck squamous carcinoma (HNSCC). Study Design: Six hundred and forty‐three incident HNSCC patients recruited through the University of Michigan Specialized Program of Research Excellence were followed for up to 5 years for survival. Participants were interviewed about personal and family cancer history, demographic information, and behavioral habits. Methods: Cox proportional hazards models were used to estimate the association between family history of cancer in a first‐degree relative and disease‐specific survival. Results: After multivariable adjustment, we found a nonsignificant inverse association between family history and HNSCC mortality (hazard ratio [HR] = 0.88, 95% confidence interval [CI] 0.57–1.35). This association was stronger and statistically significant among patients who currently both drank alcohol and smoked cigarettes at diagnosis (HR = 0.46, 95% CI = 0.22–0.97); no association was observed among participants who did not both drink and smoke at the time of diagnosis (HR = 1.14, 95% CI = 0.68–1.91; p‐interaction = 0.046). Conclusion: Results from this study suggest that having a family history of cancer may be associated with improved disease‐specific survival in patients who use tobacco and alcohol. Additional large studies, particularly in populations including nonwhites and women, are needed to confirm or refute the association and to elucidate the genetic factors that may underlie this potential association. Level of Evidence: 2b. Laryngoscope, 127:1816–1820, 2017